EVALUASI MEDICATION ERROR RESEP PASIEN RAWAT JALAN RSUD EMBUNG FATIMAH BATAM - Muliana, Hilda; Aprilla, Winda; Yuni Elfasari, Trie (JURNAL SMART ANKes, 2024)
The increasing prevalence of medication errors in the scope of pharmaceutical services is the main highlight in the world of health. Pharmaceutical service standards state that pharmaceutical services aim to protect patients and the public from irrational use of drugs, get the right treatment and improve patient life safety. Errors in the use of this drug include errors in the form of drug administration or called (medication error).This study was a retrospective observational study. Using a qualitative and descriptive research approach, namely to describe medication error which includes stages (prescribing), (transcribing), (dispensing), (administration) of this variable relationship. This research is a prescription for outpatients seeking treatment at RSUD Embung Fatimah Batam City. From July to September 2023. Prescribing was most prevalent, there was no date of birth (age) of the patient (24%) and the least was no doctor's paraf (0.43%). Transcribing did not find the amount of the assessment distribution. Dispensing incorrectly made sterile preparations (0.43%). Administration misgave a copy of the prescription (0.43%)